Strategi Pemasaran Dan Keberlanjutan Usaha: Studi Pada Usaha Nasi Kuning Di Kelurahan Tanamodindi Kota Palu - Jesiyani Junetri; Ersa Amelia Vega; Aisyah Citra; Nur Rahmayanti; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This research discusses marketing strategies and the sustainability of the yellow rice business in Tanamodindi, Palu City. Indonesia's rapid economic growth has changed people's behavior and consumption patterns, which has then increased demand for ready-to-eat food, especially yellow rice. The aim of this research is to understand the marketing strategies implemented by yellow rice entrepreneurs and their influence on business sustainability. The results of the research show that effective marketing strategies such as product differentiation, pricing and promotion are very important for the sustainability of the yellow rice business. This study suggests that entrepreneurs adopt innovative marketing strategies to remain competitive and ensure business continuity in the long term. The results of this research contribute to the existing literature on entrepreneurship, marketing and business sustainability, as well as provide insight for policy makers and entrepreneurs who wish to encourage the development of small and medium enterprises (SMEs) in Indonesia.